Effect of Whole Body Vibration Therapy on Spasticity, Balance, Fine and Gross Motor Functions in Patients with Spastic Cerebral Palsy: A Systematic Review of RCTs - Syed Ali Hussain, Zainab Hassan, Mohammad Reza Hadian Rasanani, Rabia Afzal, Nouman Khan, Hussein Mohamad Ahmad Zaib (Pakistan Journal of Medical & Health Sciences, 2023)
Context: Cerebral palsy is condition that is caused by neurological damage, which leads to problems in the somatosensory systems. It can cause spasticity in the involved muscles leading to poor function, limitations in range of motion, poor balance and coordination. Therapeutic use of whole-body vibration therapy for the management of the mentioned symptoms have been reported in the literature. This review study examines the effect of whole-body vibration on spasticity, balance and function and summarizes the effective protocols of whole-body vibration therapy for the cerebral palsy patients. Methods: Three following databases were searched comprehensively: Pubmed, PEDro and Cochrane. The selection criteria for the research papers were based on; (1) human studies with Patient-Intervention-Comparison-Outcomes-Study design (PICOS) method, according to which, P = spastic cerebral palsy; I = Whole Body Vibration; C = comparison with conventional/traditional physiotherapy; O = dynamic balance, spasticity, functional balance, fine and gross motor hand function, hand grip strength, Balance Quantification and Range of Motion; and S = Randomized controlled trials, (2) Published in English Language (3) Full Text Available (4) The PEDro scale on which the score is greater than 4 out of 10. Results: Nine RCTs were included based on the inclusion criteria. This systematic review showed that whole body vibration therapy can produce positive therapeutic effects on spasticity, balance, fine and gross motor function, muscle strength and range of motion. This modality can be used independently or in combination with the conventional physical therapy. No harm has been reported in the literature. Conclusion: It can be concluded that whole body vibration therapy is safe, cost effective and fairly simple therapeutic modality that can be used at home or in clinical settings to produce a significant change in spasticity, static and dynamic balance, motor function and range of motion. Keywords: Balance, Cerebral Palsy, Motor Function, Spasticity, Whole body vibration therapy